Pemberian Pregnant Mare Serum Gonadotropin Sebelum Perkawinan dan Jamu Selama Kebuntingan untuk Memperbaiki Performa Anak Domba (ADMINISTRATION OF PREGNANT MARE SERUM GONADOTROPIN AND JAMU DURING GESTATION TO IMPROVE FOR LAMB PERFOMANCE) - ., Andriyanto; Arif, Ridi; Winarto, Adi; Soinbala, Leo Sapelani; Achmadi, Bondan; Mustika, Aulia Andi; Pristihadi, Diah Nugrahani; ., Amrozi; Manalu, Wasmen (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Administration of pregnant mare serum gonadotropin (PMSG) hormone prior to mating increasesquality of lamb born on one and two litter sizes, but in three litter size the motality is higher. Administrationof traditional herbal medicine “jamu” consisting of ginger,green chiretta, cinnamon, Zingiberzerumbet, andpepper during gestation increases performance of lambs. This research was conducted to explore theeffectivity of PMSG injection prior to mating and jamu administration during gestation to increase lambsperformance. Eighteen priangan fat-tail ewes with weight around 20-25 kg were injected with PGF2á at adose of 10 mg/ewe twice with 11 days interval to synchronize estrous cycle. Injection of PMSG at a dose of200 IU/ewe was conducted at the second PGF2á injection. The experimental ewes were mated naturally anddivided into a randomized design with a 2 x 3 factorial arrangement with three replications. The firstfactor was dose of PMSG with two levels i.e., 0 and 200 IU/ewe. The second factor was dose of jamu withthree levels i.e., 0, 15, and 30 mL/ewe. Jamu was administered orally every week during gestation. Injectionof PMSG and administration of jamu decreased prenatal mortality, increased ratio of lamb per ewe, increased total lamb born with average birth weight and total birth weight were higher in jamu at a doseof 15 and 30 mL/ewe by 30.02 and 31.76%, repectively. During the first month postnatal, lambs born toewes injected by PMSG and administered jamu had higher number of lambs survive, average weight, totalweight around 3 times as compared to control. It was concluded that injection of PMSG prior to mating andadministration of jamu during pregnancy increase lamb birth weight and improve the quality of lamb.
Keywords: PMSG, jamu, pregnancy, performance, lamb.